ANALYSIS OF HAZARDOUS COMPOUNDS IN REFILLABLE ROLL-ON PERFUMES CIRCULATING IN GORONTALO CITY USING GC-MS - Ibrahim, Indriyanti; Isa, Ishak; Rumape, Opir; Aman, La Ode; Kunusa, Wiwin Rewini; Kilo, Jafar La; La Kilo, Akram (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2024)
This study aims to analyze the potentially hazardous compounds in refillable roll-on perfumes. The analytical method employed was GC-MS. The results from GC-MS analysis revealed hazardous compounds including Alpha-Pinene with concentrations in samples A-E = 0.0048 ppm, 0.0035 ppm, 0.0105 ppm, 0.0038 ppm, 0.0034 ppm; Dipropylene glycol with concentrations in samples A-E = 0.0322 ppm, 0.0162 ppm, 0.0692 ppm, 0.0493 ppm, 0.0465 ppm; Limonene with concentrations in samples A-E = 0.0705 ppm, 0.0373 ppm, 0.0222 ppm, 0.1462 ppm; Linalool with concentrations in samples A-E = 0.0092 ppm, 0.0568 ppm, 0.0146 ppm, 0.1298 ppm, 0.1233 ppm; Linalyl Acetate with concentrations in samples A-E = 0.1207 ppm, 0.0719 ppm, 0.0413 ppm, 0.1418 ppm, 0.1285 ppm. The levels of these compounds in the samples are below exposure thresholds, suggesting their current use is considered safe. However, stringent government oversight is necessary for refillable perfume products available in Gorontalo City.